INCLUSION EFFECT OF NUCLEOTIDE ON GROWTH AND PROTEIN RETENTION IN PACIFIC WHITE SHRIMP Litopenaeus vannamei (BOONE, 1931) - Rheido, Gestar; Mulyono, Mugi; Lubis, Amelia Sriwahyuni (Indonesian Aquaculture Journal, 2024)
Aquaculture growth is expected to continue to increase until it, intensification of vanamei shrimp culture is one of the best possibilities for increasing aquaculture production. Limited supply, price, and environmental factors are issues in meeting the needs of fish meals in feed. This study aimed to evaluate the effectiveness of nucleotides (NT, Nucleoforce AquaTM, Bioiberica, SAU, Spain) as feed additives available commercially in optimizing feed formulations from plant-based ingredients in the production of Pacific white shrimp (Litopenaeus vannamei). A 60-day growth trial was conducted to evaluate five dietary treatments: Basal-1 with 10% fish meal; Basal-2 with 6% fish meal; Diet-1: 10% fish meal+0.1% NT; Diet-2:8% fish meal+0.1% NT and Diet-3: 6% fishmeal+0.1% NT. Results showed that the inclusion of 0.1% nucleotide into the diet formulation has been able to provide good results. Adding nucleotides provides better performance and significantly increases the final biomass, final individual body weight (FBW), feed conversion ratio (FCR), feed protein retention, and average daily growth (ADG) (P<0.05) and thermal growth coefficient (TGC). The best results is Diet-1 (10% FMNT treatment) with the best protein content of 37.06% ± 0.15, showed the best performance of growth parameters (ADG, FBW, SR, TGC, PER, and RP) and lowest FCR. The addition of 0.1% nucleotide proves that the functional and nutritional properties of NT have many advantages in increasing the growth rate and more efficient in protein absorption. Therefore, 0.1% NT can be recommended as a supplement in shrimp feed.